Dexmedetomidine alleviates acute kidney injury in a rat model of veno‐arterial extracorporeal membrane oxygenation - Min Yu; Shilin Wei; Xueyang Shen; Junjie Ying; Dezhi Mu; Xiangyang Wu; Yongnan Li (Intensive Care Medicine Experimental)
Abstract Background Although extracorporeal membrane oxygenation (ECMO) is an effective technique for life support, the incidence of acute kidney injury (AKI) during ECMO support remains high. Dexmedetomidine (DEX), which has been widely used for sedation during ECMO, possesses several properties that help reduce the occurrence of AKI. This study aimed to investigate the protective effect of DEX on kidney function during ECMO. Methods A total of 18 male Sprague–Dawley (SD) rats were randomly divided into three groups: Sham, ECMO, and ECMO + DEX groups. ECMO was established through the right jugular vein for venous drainage and right femoral artery for arterial infusion and lasts for four hours. Hematoxylin and eosin staining was used to evaluate the kidney Paller score for the rats in each group. Enzyme-linked immunosorbent assay was used to measure the levels of kidney injury biomarkers and cytokines in the serum. Reagent kits were used to measure the blood urea nitrogen (BUN) and creatinine (Cr) levels, which helped determine kidney function. Immunohistochemical staining was used to evaluate neutrophil infiltration in the kidney. Results The pathological Paller score was substantially lower in the ECMO + DEX group. The levels of Kidney Injury Molecule-1 (KIM-1) and N-acetyl-β-D-glucosaminidase (NAG) were also significantly reduced. The kidney functionality, as indicated by BUN and Cr, was significantly improved compared with the ECMO group. The levels of cytokines IL-6, IL-1β, and TNF-α, were also significantly decreased in the ECMO + DEX group. Conclusion This study demonstrated that dexmedetomidine could reduce inflammatory response and alleviate AKI during ECMO support.